A Unified Theory of Weakly G-Closed Sets and Weakly G-Continuous Functions - Noiri, Takashi; Popa, Valeriu (Sarajevo Journal of Mathematics, 2024)
We introduce the notion of weakly mng-closed sets as a unified form of weakly ω-closed sets Ra, weakly rg-closed sets Na, weakly π g-closed sets RGC and weakly mg^*-closed sets No-Po4. Moreover, we introduce and study the notion of weakly mng-continuous functions to unify some modifications of weakly g-continuous functions. 2010 Mathematics Subject Classification. 54A05, 54C08